2011
DOI: 10.1002/ptr.3579
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes of the Filamentous Fungus Mucor Mucedo and Inhibition of Chitin Synthase Activity Induced by Anethole

Abstract: trans-Anethole (anethole), a major component of anise oil, has a broad antimicrobial spectrum with antimicrobial activity relatively weaker than those of well-known antibiotics, and significantly enhances the antifungal activity of polygodial and dodecanol against the baker's yeast Saccharomyces cerevisiae and human pathogenic yeast Candida albicans. However, the antifungal mechanism of anethole is unresolved. Anethole demonstrated antifungal activity against the filamentous fungus, Mucor mucedo IFO 7684, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…It is possible that the mode of chemosensitizing activity of the essential oil of O. sanctum is due to its major constituent, methylchavicol. As cited above, the antifungal activity of another phenylpropene, anethole, was by inhibition of fungal chitin synthase (Yutani et al, 2011a). The combination of inhibitors of chitin and ergosterol biosynthesis by a phenylpropene (methylchavicol) and a triazole (FLU), respectively, may undermine fungal cell wall/membrane integrity.…”
Section: Chemosensitization Of Antifungal Agentsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is possible that the mode of chemosensitizing activity of the essential oil of O. sanctum is due to its major constituent, methylchavicol. As cited above, the antifungal activity of another phenylpropene, anethole, was by inhibition of fungal chitin synthase (Yutani et al, 2011a). The combination of inhibitors of chitin and ergosterol biosynthesis by a phenylpropene (methylchavicol) and a triazole (FLU), respectively, may undermine fungal cell wall/membrane integrity.…”
Section: Chemosensitization Of Antifungal Agentsmentioning
confidence: 97%
“…However, combination of estragole with AMB was antagonistic, reducing antifungal activity against C. albicans (Shin and Pyun, 2004). It was recently shown that anethole is an inhibitor of fungal chitin synthase (Yutani et al, 2011a). Hence, the antifungal synergism between the phenylpropenes and the azoles is probably related to effectively reducing overall fungal cell wall/membrane integrity.…”
Section: Chemosensitization Of Antifungal Agentsmentioning
confidence: 99%
“…In this study, we found that anethole induced the cell death of a human opportunistic pathogenic fungus, Aspergillus fumigatus , accompanied by DNA fragmentation, which indicates apoptotic‐like cell death. Although the mechanisms underlying the antimicrobial action of anethole have not yet been elucidated in detail, we recently revealed that anethole‐induced growth inhibition with morphological changes in a filamentous fungus, Mucor mucedo , depends on the fragility of cell walls caused by chitin synthase inhibition . Additionally, the inhibition of growth of Mucor spp., including M. mucedo , caused by anethole was accompanied by swollen hyphae resulting from the direct restriction of chitin and chitosan biosynthesis .…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanisms underlying the antimicrobial action of anethole have not yet been elucidated in detail, we recently revealed that anethole‐induced growth inhibition with morphological changes in a filamentous fungus, Mucor mucedo , depends on the fragility of cell walls caused by chitin synthase inhibition . Additionally, the inhibition of growth of Mucor spp., including M. mucedo , caused by anethole was accompanied by swollen hyphae resulting from the direct restriction of chitin and chitosan biosynthesis . Chitin and chitosan are principal components of the cell wall in zygomycetes, including Mucor spp.…”
Section: Introductionmentioning
confidence: 99%
“…A previous report suggests that the morphological changes on Mucor mucedo treated with anethole (major component of anise oil) could be explained by the fragility of cell wall caused by chitin synthase inhibition (Yutani et al. ).…”
Section: Discussionmentioning
confidence: 99%